Answer:
(fog)(x) = 4x - 7
Step-by-step explanation:
f(x) = 2x-1 and g(x) = 2x-3;
(fog)(x) = f(g(x)
= f(2x - 3) = 2(2x - 3) - 1
= 4x - 6 - 1
= 4x - 7
Answer:
$120.50
Step-by-step explanation:
50 - 75 = -25
135.50 - 25 = 120.50
Study..................................................
Answer:
144 ft. i just had this question on my test .
Step-by-step explanation:
Answer:
The height of the triangle is always the measurement of a line (often shown as dashes) that is perpendicular to the base and extends to the opposite angle at the top of the triangle.
If it is a right triangle, and the right angle is at the bottom, the side extending up from the right angle will be the height. But this is not always the case.